Politics of inclusion castes, minorities, and affirmative action - Hasan, Zoya. (New Delhi ; Oxford : Oxford University Press, 2009)
Situated at the interface of policy and political processes, this study explores the dynamics and strategies of the state with regard to Muslims and lower castes. It examines the underlying issues that influence state policy towards disadvantaged groups.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Dalits -- Political activity -- India; Dalits -- Government policy -- India; India -- Scheduled tribes -- Political activity; India -- Scheduled tribes -- Government policy; Minorities -- Political activity -- India; Minorities -- Government policy -- India; Reverse discrimination in employment -- India